2021
DOI: 10.1371/journal.pone.0258144
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to lower limb performance in children and adolescents aged 7 to 17 years: A systematic review with meta-analysis

Abstract: Background The literature identifies several factors that are associated with lower limb performance (LLP). However, there is little consensus on which factors have the major associations with LLP. Objective Examine, analyze and summarize the scientific evidence on the factors associated with the performance of LLP in children and adolescents of both sexes aged between 7 and 17 years. Design This systematic review was conducted following the Preferred Reporting Items for Systematic Review and Meta-Analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Lower limb muscle strength and power are positively related to good bone health and are inversely related with cardiovascular disease and metabolic syndrome in children and adolescents [ 53 ]. Moreover, keeping satisfactory lower limb power levels during early life and adolescence leads to good physical functionality in daily living activities (DLA), such as walking/running efficiently and increasing daily movements, thus helping to reduce sedentary behavior and decrease the risk of metabolic syndrome as well as improving the quality of life [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lower limb muscle strength and power are positively related to good bone health and are inversely related with cardiovascular disease and metabolic syndrome in children and adolescents [ 53 ]. Moreover, keeping satisfactory lower limb power levels during early life and adolescence leads to good physical functionality in daily living activities (DLA), such as walking/running efficiently and increasing daily movements, thus helping to reduce sedentary behavior and decrease the risk of metabolic syndrome as well as improving the quality of life [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, adolescents with decreased muscle functions are more likely to develop insulin resistance, diabetes, dyslipidemia, and heart disease [ 40 ]. Additionally, lower limb power is positively correlated with attention levels in preschoolers and has a positive effect on school performance [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study conducted by Vandoni et al [ 46 ] on 3923 Italian adolescents aged 11–13 years found that overweight and obese adolescents exhibited a slower 5-meter repeated running speed compared to healthy participants. It is well-known that running speed is a physical ability that is directly associated with good body composition [ 47 ], better school performance [ 45 ], and protection against metabolic syndrome [ 48 ]. Therefore, the higher proportion of non-fit boys and girls (41% and 34%) in our study indicates overall health risks [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, speed is related to lower limb power and sprinting capacity, also leading to relationships with lower limb strength, which positively correlates with obesity [15], metabolic syndrome, and cardiovascular disease in children and adolescents [57]. Additionally, maintaining adequate lower limb power levels throughout early life and adolescence results in good physical functionality in daily living activities, which reduces sedentary behavior [58]. In an observational and cross-sectional study, Petrovics et al [59] analyzed a cohort of 708 adolescents (360 girls) aged 14-18 years old, and during a 4-year follow-up, they found worsened lower limb power in the obese and overweight boys and girls.…”
Section: Discussionmentioning
confidence: 99%